Generic limits in South American stag beetles: taxa currently misplaced in Sclerostomus Burmeister (Coleoptera: Lucanidae: Lucaninae: Sclerostomini) - Grossi, Paschoal C.; Paulsen, M. J. (Zootaxa, 2009)
The genus Sclerostomus Burmeister (Lucanidae: Lucaninae) of South America is redefined and restricted to species with a complex male genital capsule. Subgenera of Sclerostomus that lack this character are elevated to generic status, including Altitatiayus Weinreich with 5 species, Chileistomus Weinreich with 1 species, and Sclerostomulus Weinreich with 2 species. These genera are redescribed, and 2 new monotypic genera are created for species of Sclerostomus that cannot be accommodated into these existing genera. The subgenus Sclerostominus Weinreich is synonymized with Sclerostomus. Three species with simple male genitalic capsules are transferred to the genus Onorelucanus Bartolozzi & Bomans, resulting in the new combinations O. boileaui (Weinreich), O. marujae (Arnaud, Noguchi, & Bomans), and O. noguchii (Arnaud & Bomans). One species is transferred to Onorelucanus from the genus Scortizus Westwood, resulting in the combination O. pulverosus (Westwood). Scortizus ismaeli Fukinuki is placed in synonymy with O. pulverosus (Westwood).